Oestrogen-induced epithelial-mesenchymal transition (EMT) in endometriosis: Aetiology of vaginal agenesis in Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome - Lih Yuan, Too; Sulaiman, Nadiah; Nur Azurah, Abdul Ghani; Maarof, Manira; Rabiatul Adawiyah Razali,; Yazid, Muhammad Dain (Frontiers in Physiology, 2022)
Endometriosis occurs when endometrial-like tissue forms and grows outside the uterus due to oestrogen-induced epithelial-mesenchymal transition in the female reproductive tract. Factors that suppress this event could become potential therapeutic agents against disease occurrence and progression. However, an overview of these studies is still lacking. This review assessed the impact of a number factors on oestrogen-mediated epithelial-mesenchymal transition in the emergence of several diseases in the female reproductive tract, primarily endometriosis. The association between epithelial-mesenchymal transition and Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome was also investigated. Oestrogen, Wnt4 and epithelial-mesenchymal transition were chosen as keywords in Scopus, PubMed, and Web of Science searches performed on 28th June 2021. Study selection was refined to cancer-irrelevant, English, original articles published between years 2011 to 2021. The full-text assessment was carried out for topic-related articles after title and abstract screening. Included studies were summarised and assessed for their risk of bias using the Office of Health Assessment and Translation tool. In this review, 10 articles investigating oestrogen and epithelial-mesenchymal transition in the female reproductive tract were summarised and classified into two groups: seven studies under ‘factor’-modulated epithelial-mesenchymal transition and three studies under ‘factor’-manipulated oestrogen-induced epithelial-mesenchymal transition. The current evidence proposes that epithelial-mesenchymal transition is one of the prime causes of reproductive-related disease. This event could be mediated by distinct stimuli, specifically oestrogen and Wnt4 aberration. The results of this review suggest that oestrogen and Wnt4 participate in epithelial-mesenchymal transition in vaginal epithelial cells in MRKH syndrome, adopting from the theories of endometriosis development, which could therefore serve as a foundation for novel target treatment, specifically related to vaginal epithelialisation, to ensure better surgical outcomes.